Elevational patterns of Polylepis tree height (Rosaceae) in the high Andes of Peru: role of human impact and climatic conditions - Kessler, Michael; Toivonen, Johanna M.; Sylvester, Steven P.; Kluge, Jürgen; Hertel, Dietrich (Frontiers in Plant Science, 2014)
We studied tree height in stands of high-Andean Polylepis forests in two cordilleras near Cuzco (Peru) with respect to variations in human impact and climatic conditions, and compared air and soil temperatures between qualitatively defined dry and humid slopes. We studied 46 forest plots of 100 m2 of five Polylepis species at 3560-4680 m. We measured diameter at breast height (dbh) and tree height in the stands (1229 trees in total), as well as air and soil temperatures in a subset of plots. The data was analysed combining plots of given species from different sites at the same elevation (±100 m). There was no elevational decrease of mean maximum tree height across the entire data set. On humid slopes, tree height decreased continuously with elevation, whereas on dry slopes it peaked at middle elevations. With mean maximum tree heights of 9 m at 4530 m on the humid slopes and of 13 m at 4650 m on the dry slopes, we here document the tallest high-elevation forests found so far worldwide. These highest stands grow under cold mean growing season air temperatures (3.6 °C and 3.8 °C on humid vs. dry slopes) and mean growing season soil temperatures (5.1 °C vs. 4.6 °C). Mean annual air and soil temperature both decreased with elevation. Dry slopes had higher mean and maximum growing season air temperatures than humid slopes. Mean annual soil temperatures did not significantly differ and mean annual air temperatures only slightly differed between slopes. However, maximum air temperatures differed on average by 6.6 K between dry and humid slopes. This suggests that the differences in tree height between the two slopes are most likely due to differences in solar radiation as reflected by maximum air temperatures. Our study furthermore provides evidence that alpine Polylepis treelines grow under lower temperature conditions than global high-elevation treelines on average, suggesting that Polylepis species may have evolved special physiological adaptations to low temperatures.